Ecological correlates of rare Cape Proteaceae, South Africa, and the implications for their conservation - Brown, Susan Ann (Department of Biological Sciences, 2016)
This thesis examines the ecology of rare Proteaceae of the Fynbos Biome. South Africa. The aim was to determine whether there are any unifying ecological parameters which might be significant for their conservation. The current status of all Cape Proteaceae was initially assessed. A total of 124 taxa were ascribed the I U C N status of recently extinct (3 taxa), endangered (33 taxa), vulnerable (29 taxa) and naturally rare (59 taxa). The distributions of rare taxa are characteristically small in size and range, 59 taxa occurring in only one or two populations and 63 taxa being restricted to a range of less than 5 km². Small nature reserves are proposed for the protection of such restricted taxa. An examination of the distribution of all the rare taxa shows exceptionally high concentrations in the Cape Town urban area and the lowlands north of Cape Town. This indicates the need for conservation considerations by urban and regional planners in the long term development of this area. Naturally rare taxa exhibit nodes (areas of high concentrations) over the centres of well-defined centres of endemism. Such areas merit conservation as representative and diverse habitats of fynbos plant species. Threats occurring at rare Proteaceae sites were recorded. An inappropriate fire interval and invasion by the Argentine ant. Iridomyrmex humilis, were shown to be the probable cause of rarity in Proteaceae exhibiting short lifespans and myrmecochorous seed stores. The monitoring of fire intervals at rare Proteaceae sites and the removal of the Argentine Ant are considered priorities for conservation management of rare Proteaceae.